What is Matter to Improve Employees’ Performance? An Evaluation on State Civil Servant Officers at Environmental Services Within Deli Serdang Regency - Purba, Kuras (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Each company days by days always strives to achieve their best performance through their employees. There were many factors that affect employee performance such as motivation and workload in which has been researched overtime. Work motivation in government services could support human behavior so that they want to work hard and enthusiastically to achieve optimal results. Excessive workload however, cause an uncomfortable working atmosphere for workers. This research aimed to evaluate how optimize human performance within governmental organization. We conducted a quantitative approach by using census approach. The respondents of this study were 37 state civil servant officers in the Environmental Service of Deli Serdang Regency. Data obtained through interviews using a questionnaire. Consent was taken in this research. The data analysis technique uses validity, reliability, classical assumption test (normality, multicollinearity, heteroscedasticity and linear) and hypothesis testing (path analysis technique and Sobel test). The results showed that motivation and workload had a positive and significant effect on job satisfaction. Motivation and workload also have a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Motivation and workload have a positive effect on employee performance through job satisfaction on the employees of the Environmental Service Office of Deli Serdang Regency.